Stagnation-point Flow of a Hybrid Nanofluid Over an Exponentially Stretching Sheet with Zero Mass Flux Boundary Condition - N. A. Halim; N. S. A. Affrizal; N. I. M. Amin (International Journal of Integrated Engineering, 2024)
Research on boundary layer flow and heat transfer characteristics of hybrid nanofluid over exponential stretching surface using the modified Buongiorno nanofluid model (MBNM) with zero mass flux is still lacking. The model takes into consideration the effect of Brownian motion and thermophoresis as well as the effective properties of a hybrid nanofluid. The imposed zero normal flux condition assumes that the nanoparticle volume fraction on the surface is controlled passively via temperature gradient. The governing partial differential equations (PDEs) are transformed into ordinary differential equations (ODEs) using appropriate similarity variables before being solved numerically using bvp4c in MATLAB. Obtained results are presented in graphical and tabular form. An 8.82% increment was observed in the values of Nusselt numbers of hybrid nanofluid as compared to base fluid. The stagnation parameter and nanoparticle volume fraction are important factors in improving the heat transfer rate of the fluid. The Nusselt number is an increasing function of both parameters. Meanwhile, the Brownian motion parameter has a negligible effect on the heat transfer rate.